2014
DOI: 10.1097/mcp.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy and cystic fibrosis

Abstract: The role of physiotherapy in CF is complex and includes airway clearance, exercise, and management of the long-term sequelae of musculoskeletal issues. More rigorous physiotherapy studies are required to assist with evidence based practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
(15 reference statements)
0
32
0
3
Order By: Relevance
“…Alda Marques 1,2* , Joana Cruz 1,2 , Cristina Jácome 1,2 and Ana Oliveira 1,2 *Address all correspondence to: amarques@ua.pt…”
Section: Author Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alda Marques 1,2* , Joana Cruz 1,2 , Cristina Jácome 1,2 and Ana Oliveira 1,2 *Address all correspondence to: amarques@ua.pt…”
Section: Author Detailsmentioning
confidence: 99%
“…Respiratory physiotherapy is a non-pharmacological treatment commonly provided to patients with cystic fibrosis (CF) [1]. According to international guidelines, respiratory physiotherapy is a key element of care for patients with CF, as it aims at both rehabilitation and prevention [2].…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy is an integral part of the treatment of CF [ 2 ] and the clinical efficacy of airway clearance is well established [ 3 ][ 4 ][ 5 ][ 6 ]. According to a recent Cochrane systematic review, no single airway clearance technique has shown superiority [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several long-term studies have looked at the efficacy of different airway clearance techniques and reported a positive impact on airway clearance in maintaining health with no technique being superior to another. 11 Some authors claim that certain airway clearance techniques could exacerbate GOR and even suggest that postural drainage with a head-down tilt is contra-indicated in patients with GOR. 12,13 Intrapulmonary percussive ventilation (IPV) delivers small bursts of high-flow gas at 100-300 cycles/min, which causes a counterflow and vibrations of the airway walls.…”
Section: Introductionmentioning
confidence: 99%